A distributed fuzzy logic-based root selection algorithm for wireless sensor networks. (January 2015) - Alaybeyoglu, Aysegul
Abstract: In this study, a distributed fuzzy logic (DFL) method with five input parameters namely, energy, centrality, distance to base station, number of hops and node density is proposed for efficient root election system. In order to prevent high energy consumption during message transmission, we made each node run fuzzy logic engine distributedly. We decrease the number of message transmissions from member nodes to root node by running DFL on intermediate nodes and by eliminating the messages of nodes that have less probability to be selected as a new root. The proposed system also includes fault tolerance, load balance, timeliness and the scalability mechanisms. To prove the efficiency of our algorithm, we compared it with the algorithms namely; Low Energy Adaptive Clustering Hierarchy (LEACH), Adaptive Clustering Algorithm via Waiting Timer (ACAWT), Cluster Head Election mechanism using Fuzzy logic (CHEF) and Gupta's Algorithm.